Reproductive performance of prepubertal Bos indicus heifers after progesterone-based treatments - Claro Junior, I. [UNESP]; Sa Filho, O. G. [UNESP]; Peres, R. F. G. [UNESP]; Aono, F. H. S. [UNESP]; Day, M. L.; Vasconcelos, José Luiz Moraes [UNESP] (Elsevier B.V., 2010)
The objective was to evaluate the effects of exogenous progesterone (P4) on reproductive performance of prepubertal Bos indicus heifers. Prepubertal Nelore heifers (n = 589; 24.0 +/- 1.13 mo; 298.0 +/- 1.89 kg; body condition score of 3.2 +/- 0.26; mean +/- SEM) were randomly assigned to receive, between experimental Days -12 and 0: no treatments (CIDR0; n = 113); a new intravaginal insert (CIDR) containing 1.9 g of P4 (CIDR1; n = 237); or a similar insert previously used three times, with each use occurring for 9 d (CIDR4; n = 239). An additional treatment group was pubertal heifers given 12.5 mg dinoprost tromethamine im on Day 0 (PGF; n = 346), and used as controls for evaluation of conception rates. on Day 0, transrectal palpation was done for uterine score evaluation (UtS; 1-3 scale), blood samples were taken for serum P4 concentrations, and follicle diameter (FD) was measured. The breeding season started on Day 1 and consisted of AI after detection of estrus between Days I and 45, and exposure to bulls between Days 46 and 90. There were effects of treatment (P < 0.05) on serum concentrations of P4 on Day 0 (0.37 +/- 0.16, 2.31 +/- 0.11, and 1.20 +/- 0.11 ng/mL for CIDR0, CIDR1, and CIDR4, respectively; mean SEM), FD on Day 0(9.45 +/- 0.24, 9.72 +/- 0.17, and 11.42 +/- 0.16 mm), UtS on Day 0 (1.49 +/- 0.06, 1.88 +/- 0.04, and 2.24 +/- 0.04), estrus detection rates at 7 d (19.5, 42.6, and 38.3%) and 45 d (52.2, 72.1, and 75.3%) of the breeding season, and on pregnancy rates at 7 d (5.3, 14.3, and 18.4%), 45 d (27.4, 39.2, and 47.7%) and 90 d (72.6, 83.5, and 83.7%) of the breeding season. Conception rate 7 d after the start of the breeding season was greater (P < 0.05) in heifers from the CIDR4 (46.8%) and PGF (43.8%) groups than in the CIDR0 (27.3%) and CIDR1 (33.7%) groups. In conclusion, exogenous P4 hastened puberty and improved pregnancy rates at the beginning of the breeding season in prepubertal Bos indicus heifers. Furthermore, previously used CIDR inserts were better than new inserts. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Puberty; Progesterone; Pregnancy rates; Bos indicus; Zebu cattle